Renal Cystic Nephroma: Histologic and Immunohistochemical Analyses and Review of Literature - M, Darouichi; JP, Till; PE, Constanthin (Archives of Clinical and Biomedical Research, 2019)
Background: A case of renal Cystic Nephroma (CN) was reported in 32 years-old women presenting with an incidental renal mass on radiological imaging. Methods: On CT-scan examination, a renal cell carcinoma was suspected and right nephrectomy was performed. The resected tumor measured 17 × 10 × 7 cm. Macroscopically, the tumor was a multilocular mass with cysts ranging from 0.5 cm to 4.5 cm. The tumor was well delineated relative to non-tumoral renal parenchyma, which was physiological in appearance with a cortex at 1 cm without evidence of infiltration of the tumor. At the hilum, the arterial, venous and ureter were normal. No lymph node was identified. Microscopically, the lesion was well defined by a fibrous capsule, consisting of multiple cystic formations of variable sizes bordered by a mono-stratified epithelium, which ranged from flat to cubic. The lining epithelial cells had a hobnail appearance, abundant cytoplasm and an oval nucleus associated with a nucleolus. No mitosis were founded. The cysts were subtended by cellular fibrous septa of ovarian type. On immunohistochemical examination, the epithelial cells were positive for cytokeratins 7 and 19; stromal cells were positive for estrogen receptors, progesterone receptor and CD10. In the septa, there were some bundles of smooth muscle cells positive for desmin and smooth muscle actin. Conclusion: The patient was alive 8 years after treatment, without metastasis or recurrence. Histologic and immunohistochemical analyses may be helpful in differential diagnosis between benign cystic renal neoplasms, CN, mixed epithelial and stromal tumor (MEST) and malignant tumors such as clear cell renal carcinoma (CCRC) in adults.